Efektivitas ekstrak kelenjar hipofisa ikan Mas (Cyprinus carpio L) terhadap pamatangan gonad akhir ikan Betok (Anabas testudineus Bloch).Efektivitas ekstrak kelenjar hipofisa ikan Mas (Cyprinus carpio L) terhadap pamatangan gonad akhir ikan Betok (Anabas - S Suriansyah (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2020)
Extract of the pituitary gland can affect gonad maturation through control of GnRH and LH release, which hypothalamus releases GtH, and subsequently pituitary gland secretes luteinizing hormone (LH) triggerring steroid hormones on gonad final maturation. The specific objective of this study was to examine the effectiveness of the pituitary gland extract for final gonad maturation of climbing perch fish. Benefit of this research was as a contribution to the technology development of climbing perch fish breeding on peat swamp waters. Administration of pituitary gland extract 0.002 ml/g the increase in final total diameter distribution proportion climbing perch fish egg 0.7 mm by 80%, egg nucleus position proportion into germinal vesicle breakdown (GVBD) by 85% and increase the value of GSI that was 4.7%. Keywords : Pituitary gland extract, final gonad maturation.